The Nigerian Government’s Strategies and the Question of Enduring Peace for Conflict Management - Usoro, Abosede Abimbola; Ekpenyong, Okon Effiong; Effiong, Charles (Current Aspects in Business, Economics and Finance Vol. 3, 2022)
The article x-rayed the conflict management strategies that Nigerian government adopted in resolving the crises in Odi and the larger Niger Delta region of Nigeria. The study undertook an extensive review of literature related to these two conflict situations to determine which of these strategies - the use of force or the granting of amnesty worked better for the benefit of Nigeria. It has been noted that using force to resolve the Niger Delta squabbles has invariably intensified the conflict. On the other side, the granting of amnesty provided a better platform for conflict management and has the ability to resolve the Niger Delta conflicts if pursued energetically and holistically. Key recommendations were that: the root cause(s) of the conflicts should be well established to know the strategies to use in managing it; the managers of conflicts should not rush and employ force to manage any conflict; there should always be active channels for effective communication between the conflicting parties while equitable, just socio-political environment should always be created to forestall the emergence of conflict. Finally, leaders should always be proactive on conflict resolutions through effective communication and dialogue not until when there is a breakdown of law and order.